2021
DOI: 10.24234/wisdom.v19i3.506
|View full text |Cite
|
Sign up to set email alerts
|

Gender Markers in the English Picture of the World

Abstract: Gender is determined as an ideological frame that assembles the idea of what it means to be a man or a woman in a certain culture, a non-linguistic category with linguistic ways of actualization. The article substantiates the key theoretical problems concerning gender-marking based on English phraseology and their influence on the formation of the gender picture of the world. The objective of the current paper is to analyze gender-marked phraseological units of the English language, which are the basic matrice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…All scholars agree that the semantics of a phraseological unit correlates with the culture code shared by the speaker and listener. For instance, the analysis of English gender-marked phraseological units revealed that gender stereotypes govern the national linguistic worldview formation to a great extent encoding the inequality between men and women (Humeniuk, 2021). The comparative study of the gender representation in Tatar and English phraseological units revealed that the female component in both languages frequently conveys a negative connotation (Khuzina & Mukhtarova, 2018).…”
Section: Review Papermentioning
confidence: 99%
See 2 more Smart Citations
“…All scholars agree that the semantics of a phraseological unit correlates with the culture code shared by the speaker and listener. For instance, the analysis of English gender-marked phraseological units revealed that gender stereotypes govern the national linguistic worldview formation to a great extent encoding the inequality between men and women (Humeniuk, 2021). The comparative study of the gender representation in Tatar and English phraseological units revealed that the female component in both languages frequently conveys a negative connotation (Khuzina & Mukhtarova, 2018).…”
Section: Review Papermentioning
confidence: 99%
“…Grammatical categories seem to reveal a connection with human cognitive activity, which was proved by the research results (8 papers). In particular, these studies examine the role of the grammatical category of animacy-inanimacy of nouns in creating the Russian linguistic worldview (Narushevich & Bak, 2021), gender markers in language (Gulik, 2015;Humeniuk, 2021;Khuzina & | Review Paper Mukhtarova, 2018) and the function of the Russian pronoun 'I' in phraseological units (Graneva, 2021) as well as the opposition of the Russian pronouns 'we' and 'they' (Revenko & Osetrova, 2019). The medieval linguistic worldview was analysed in terms of its influence on the morphological system of verb tenses in the modern Slavic languages (Shumilo, 2021).…”
Section: Review Papermentioning
confidence: 99%
See 1 more Smart Citation